Two neurocognitive domains identified for patients with myalgic encephalomyelitis/chronic fatigue syndrome and post-acute sequelae of COVID-19 - Ariadna Sandoval; Mingqi Li; Leonard A. Jason (Frontiers in Neurology)
Patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and Post-Acute Sequelae of COVID-19 (PASC) often have neurocognitive complaints that involve memory and concentration problems and difficulties paying attention. Other neurocognitive domains such as hypersensitivity to noise and light have rarely been included as aspects of neurocognitive impairment for these post-viral conditions. The current study evaluated a more extensive list of neurocognitive items for a group of 2,313 patients with ME/CFS and 299 patients with PASC. Exploratory factor analyses found two factors for each patient group, one involving classic memory and concentration symptoms and the other involving sensory overload phenomena. The findings suggest that researchers might consider expanding the types of self-report neurocognitive symptoms among patients with these post-viral illnesses.